The Use of Drill Method with Wall Media Improves Volleyball Passing Skills of Students of State Senior High School 1 Sentani, Jayapura - Armianto David Hukubun; Marsuki, Marsuki; Heppy Hein Wainggai (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
The research was conducted at Senior High School (SMA) Negeri 1 Sentani, Jayapura Regency, in class XI Natural Sciences (IPA) 4. As many as 35% of students still have difficulty in passing volleyball with less precise accuracy. The purpose of this study was to assess the effect of drill method training using wall media on volleyball carry passing results. This research is an experimental study with a pre-test and post-test design. At the pre-test stage, students were scored based on the number of successful balls into the box, with an average value of 0.554 and a standard deviation of 3.228. At the post-test stage, students' scores were analyzed again with a mean value of 1.056 and a standard deviation of 6.156. The normality test results showed a significance value of 0.487 (>0.05), indicating that the residual distribution of the data was quite normal. Furthermore, the homogeneity test shows a significance value of 0.451 (>0.05), which indicates that the data variance is homogeneous. Furthermore, the hypothesis test shows a significance value of 0.04 (<0.05), indicating a significant influence on variable X. In addition, the calculated t value of 3.095 (>1.96) indicates a significant influence on variable Y. The results showed an increase in training results by 33% in volleyball carry passing for students in class XI IPA 4 SMA Negeri 1 Sentani, Jayapura Regency, using the drill training method using wall media.